1.What is the correct reason for statement 2?Prove: 2(w + 6) + 4 = 2w + 16
Statements Reasons
1. 2(w + 6) + 4 1. Given
2. (2w + 12) + 4 2. ?
3. 2w + (12 + 4) 3. Associative Property
4. 2w + 16 4. Addition

2.What is the correct reason for statement 2?
Prove: 4 + 3x + (x ∙ 2) = 5x + 4
Statements Reasons
1. 4 + 3x + (x ∙ 2) 1. Given
2. 4 + 3x + 2x 2. ?
3. 4 + 5x 3. Addition
4. 5x + 4 4. Commutative Property


3.What is the correct reason for statement 3?
Prove: (11m) ∙ 4 + m = 45m
Statements Reasons
1. (11m) ∙ 4 + m 1. Given
2. 4 ∙ (11m) + m 2. Commutative Property
3. (4 ∙ 11) ∙ m + m 3. ?
4. 44m + m 4. Commutative Property
5. 45m 5. Addition

4.What is the correct reason for statement 5?
Prove: k + 4 + 6(1 + k) = 11k + 10
Statements Reasons
1. k + 4 + 6(1 + k) 1. Given
2. k + 4 + (6+ 6k) 2. Distributive Property
3. k + (4 + 6) + 6k 3. Associative Property
4. k + 10 + 6k 4. Addition
5. k + 6k + 10 5. ?
6. 7k + 10 6. Addition

5.Select the correct reasons for statements 1 and 3 to complete the proof.
Prove: 3x + 2 • x • 11 = 25x.
1. 3x + 2 • x • 11 = 3x + 2 • 11 • x 1. ?
2. 3x + 2 • x • 11 = 3x + 22x 2. Multiplication
3. 3x + 2 • x • 11 = 25x 3. ?

Answers

Answer 1
Answer: 1. The reason for statement 2 is
Distributive Property

2. The reason for statement 2 is
Commutative Property

3. The reason for statement 3 is
Associative Property

4. The reason for statement 5 is
Commutative Property

5. The reason for statement 1 is
Associative Property
The reason for statement 3 is
Addition
Answer 2
Answer:

State the correct reason for each statement

  • 2(w + 6) + 4 = 2w + 16

1. 2(w + 6) + 4

2. (2w + 12) + 4

3. 2w + (12 + 4)

4. 2w + 16

Statements Reasons:

1. Given

2. distributive property

3. Associative Property

4. Addition

  • 4 + 3x + (x ∙ 2) = 5x + 4

1. 4 + 3x + (x ∙ 2).

2. 4 + 3x + 2x

3. 4 + 5x

4. 5x + 4

Statements Reasons:

1. Given

2. cummulative property

3. Addition

4. Commutative Property

  • (11m) ∙ 4 + m = 45m

1. (11m) ∙ 4 + m

2. 4 ∙ (11m) + m

3. (4 ∙ 11) ∙ m + m

4. 44m + m.

5. 45m

Statements Reasons:

1. Given

2. Commutative Property

3. associative

4. Commutative Property

5. Addition

  • k + 4 + 6(1 + k) = 11k + 10

1. k + 4 + 6(1 + k)

2. k + 4 + (6+ 6k)

3. k + (4 + 6) + 6k

4. k + 10 + 6k

5. k + 6k + 10

6. 7k + 10

Statements Reasons:

1. Given

Given 2. Distributive Property

Given 2. Distributive Property 3. Associative Property

Given 2. Distributive Property 3. Associative Property 4. Addition

Given 2. Distributive Property 3. Associative Property 4. Addition 5. cumulative

6. Addition

  • 3x + 2 • x • 11 = 25x.

1. 3x + 2 • x • 11 = 3x + 2 • 11 • x

2. 3x + 2 • x • 11 = 3x + 22x

3. 3x + 2 • x • 11 = 25x

Reasons:

1. associative

1. associative2. Multiplication

1. associative2. Multiplication 3. addition

Read more:

brainly.com/question/24730587


Related Questions

Solve for x. 2003-05-04-00-00_files/i0060000.jpg
3/8 divided by 1/2 =
Rite an equation of a line parallel to line EF in slope-intercept form that passes through the point (2, 6).E Oy=2x+3 Oy = 3x + 6 F Oy=-3x+23 Oy=-3x+6 22
A light bulb manufacturer randomly tests 1500 bulbs and finds that 2 are defective. How many defective bulbs would be expected in a shipment of 24,000 bulbs?A.32B.48C.120D.750
Match the function with its value f(x)= x2-3x+3 g(x)= 2x2-1 f(z^2)= .....

Ali wants to buy a piano. the piano measures 19/4 feet long. she has a space 5 feet

Answers

She'll have enough room cause 19/4 needs to be a mixed number, which is 4 3/4 feet.
Hope this helps C=

Evaluate the expression when m=4 and n=31.
n-3m

Answers

Answer:

19

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Step-by-step explanation:

Step 1: Define

Identify

m = 4

n = 31

n - 3m

Step 2: Evaluate

  1. Substitute in variables:                                                                                     31 - 3(4)
  2. Multiply:                                                                                                             31 - 12
  3. Subtract:                                                                                                            19

Hi there!  

»»————- ★ ————-««

I believe your answer is:  

19

»»————- ★ ————-««  

Here’s why:

⸻⸻⸻⸻

\boxed{\text{Calculating the Answer...}}\n\nn-3m;\text{ } m= 4, n = 31\n---------\n\rightarrow 31-3(4)\n\n\rightarrow 31 - 12\n\n\rightarrow \boxed{19}

⸻⸻⸻⸻

»»————- ★ ————-««  

Hope this helps you. I apologize if it’s incorrect.  

The two-way table shows the distribution of book style to genre. Miguel claims that given that the book is paperback (PB) does not affect the outcome that the book is nonfiction (NF).

Answers

Answer:

Yes, the two events are independent because P(NF|PB)=P(NF).

Step-by-step explanation:

How many degrees Celsius is 51°F?

Answers

Answer:

10.56

Step-by-step explanation:

51°F − 32) × 5/9 = 10.56°C

Answer:

10.56°C

Step-by-step explanation:

Hope this helps!

Simplify 81^1/2
Please simplify and show steps

Answers

a^(n)/(m)=\sqrt[m]{a^n}\n\n\n81^(1)/(2)=√(81)=9\n\n\n81^(1)/(2)=(9^2)^(1)/(2)=9^{2\cdot(1)/(2)}=9

The expression 81⁽¹/²⁾ simplifies to 9.

To simplify the expression 81¹/², we can evaluate the squareroot of 81.

The square root of a number x is a value that, when multiplied by itself, gives x. In this case, we're looking for the number that, when squared, equals 81.

The square root of 81 is 9 since 9 x 9 = 81.

Therefore, 81⁽¹/²⁾ simplifies to 9.

In terms of steps, we can represent the process as follows:

1. Recognize that 81⁽¹/²⁾ represents the square root of 81.

2. Evaluate the squareroot of 81, which is 9.

3. Thus, 81^(1/2) simplifies to 9.

By simplifying the expression, we find that 81⁽¹/²⁾is equal to 9.

To learn more about the expression;

brainly.com/question/24242989  

#SPJ6

Three times a number increases by 15 is equal to 30

Answers

Answer:       The number is 5.

Step-by-step explanation:

First, let d be our number.

Since we know that d is our number, we rewrite the expression this way:

3 times d incresed by 15 is 30.

3 times d is 3d; 3d increased by 15 => 3d + 15. This equals 30:

3d + 15 = 30

To solve for d, subtract 15 from both sides:

3d = 15

Next, divide both sides by 3:

d = 5

Using the equation 3x+15=30 x being the number we are trying to find out we replace x with 5 as 3*5 is 15+15 = 30